2017
DOI: 10.1051/0004-6361/201630159
|View full text |Cite
|
Sign up to set email alerts
|

Cold and warm electrons at comet 67P/Churyumov-Gerasimenko

Abstract: Context. Strong electron cooling on the neutral gas in cometary comae has been predicted for a long time, but actual measurements of low electron temperature are scarce. Aims. Our aim is to demonstrate the existence of cold electrons in the inner coma of comet 67P and show filamentation of this plasma. Methods. In situ measurements of plasma density, electron temperature and spacecraft potential were carried out by the Rosetta Langmuir probe instrument, LAP. We also performed analytical modelling of the expand… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(72 citation statements)
references
References 70 publications
6
66
0
Order By: Relevance
“…For this case, with the sensitivity of the comparison method, n h =1500 ± 150 cm −3 , n c ≃2730 ± 150 cm −3 , T h =6 ± 1.5 eV, and T c =0.06 ± 0.01 eV. The derived temperatures are consistent with the typical temperatures of warm and cold cometary electrons measured with the Langmuir Probe during the Rosetta mission (Eriksson et al, ).…”
Section: Discussionsupporting
confidence: 83%
“…For this case, with the sensitivity of the comparison method, n h =1500 ± 150 cm −3 , n c ≃2730 ± 150 cm −3 , T h =6 ± 1.5 eV, and T c =0.06 ± 0.01 eV. The derived temperatures are consistent with the typical temperatures of warm and cold cometary electrons measured with the Langmuir Probe during the Rosetta mission (Eriksson et al, ).…”
Section: Discussionsupporting
confidence: 83%
“…Finally, we have found that a population of cold ( 0.1 eV) electrons, first shown by Eriksson et al () to be intermittently present at Rosetta, is in fact observed consistently throughout the diamagnetic cavity. Already immediately outside the cavity, sweeps lacking a signature of cold electrons begin to turn up intermittently.…”
Section: Discussionsupporting
confidence: 70%
“…In addition to these warm electrons, clear signatures of cold ( 0.1 eV) electrons have also been observed by LAP (Engelhardt et al, ; Eriksson et al, ) and MIP (Gilet et al, ). In LAP, these show up in high‐time‐resolution current measurements at fixed bias voltage in the form pulses of typical duration between a few seconds and a few minutes, and in bias voltage sweeps in the form of very steep slopes in the current‐voltage curve at high positive bias voltages (to be discussed further below).…”
Section: Introductionmentioning
confidence: 86%
“…In this paper, we investigate the pulses of high plasma density observed outside the diamagnetic cavity by Eriksson et al (2017) while Hajra et al (2018) studied plasma density pulses inside the diamagnetic cavity. These pulses, where the density is higher than the background density have a relatively short duration, typically a few seconds to a few tens of seconds, as seen from the spacecraft.…”
Section: Introductionmentioning
confidence: 99%